CIPP-Based Evaluation of the Tahfidz Al-Qur'an Program at SMP Khadijah Surabaya - Muntafi'ah, Umi; Kusaeri, Kusaeri (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This study aims to evaluate the extent to which the tahfidz program at Khadijah Junior High School is planned, how the learning method is implemented effectively, and the impact on its output so that the profile of Khadijah Junior High School graduates can be said to be successful in becoming huffadz. The approach used in this research is a qualitative approach, data collection techniques through observation methods and interviews with the Vice Principal for curriculum, tahfidz teachers and students of SMP Khadijah. The CIPP (Context, Input, Process, Product) evaluation model in the context of this research is to explore the extent of the targets or goals, plans, actions and graduates of the tahfidz program at Khadijah Junior High School. The results of this study prove that; 1) Context evaluation, shows that this program has quality and quantity targets set in the strategic plan of the Khadijah foundation, 2) Input evaluation, Tahfidz program is planned systemically with clear and detailed planning. 3) Process evaluation, tahfidz learning activities are well organized, organized by the division of tahfidz classes tailored to the competence of students' Al-Qur'an reading, 4). Product Evaluation, Khadijah Junior High School graduates exceed the strategic plan target. Challenges that need to be considered in this tahfidz program include motivating students to be interested in participating in the tahfidz program and clarity of memorization targets.